ANALISIS PREDIKSI KEBANGKRUTAN PERUSAHAAN JASA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) MENGGUNAKAN METODE ANALISIS ALTMAN Z-SCORE - Maria Dou; Sri Hermuningsih; Gendro Wiyono (Journal Competency of Business, 2018)
This study aims to find out the level of bankruptcy connected by the hotel, restaurant and tourism sub-sector service companies using the Altman Z-Score method analysis tool. This research is included in descriptive research. The sample of this research is the hotel, restaurant and tourism sub-sector service companies listed on the Indonesia Stock Exchange (BEI) from 2014-2018. The sampling technique uses documentation techniques, namely by collecting data, analyzing data, and analyzing secondary data taken from the company's financial statements. The number of samples taken was three companies during the five years period of the current year. Data analysis was taken in accordance with financial ratios in the Altman Z-Score analysis method. The results showed that the companies selected were on average in bankruptcy / gray areas prone areas in accordance with the results of the acquisition of the Z-Score value specified in Altman Z-Score analysis method.